Magnetite and silica-coated magnetite nanoparticles are highly biocompatible on endothelial cells in vitro. (16th March 2017) - Catalano, Enrico; Miola, Marta; Ferraris, Sara; Novak, Saša; Oltolina, Francesca; Cochis, Andrea; Prat, Maria; Vernè, Enrica; Rimondini, Lia; Follenzi, Antonia
Abstract: Superparamagnetic iron oxide nanoparticles (MNPs) have recently been investigated for biological applications with promising results, owing to their ability to be targeted and heated by magnetic fields. Silica is a very suitable coating material for MNPs, facilitating the loading of targeting moieties and drug delivery. However, the potential toxicity of SiO2 -coated MNPs remains a major concern for clinical application. The synthesis, via wet-chemistry, and physico-chemical characterization of Fe3 O4 and silica coated (Fe3 O4 -SiO2 ) MNPs are here described, examining in vitro cytocompatibility including viability, necrosis, intracellular reactive oxygen species (ROS) generation and apoptosis, in an endothelial cell model. The results showed that both types of SPION are spherical, 10–15 nm in diameter and can be dispersed in water-based media. In vitro characterization revealed both to be highly cytocompatible at 10 μ g ml −1 concentration, suggesting their safe use in biomedical applications. Cytotoxicity, including ROS generation and expression of apoptosis activating enzymes (caspase 3), slightly increased at 80 μ g ml −1, in a dose dependent manner. Fe3 O4 -SiO2 nanoparticles induced a higher level of ROS and expression of caspase 3. In conclusion data suggest that both SPION types may be differently aimed in biomedical application in relation to the dose, acting as biocompatible materials, as component of scaffolds, or as a device for theranostics.